2023
DOI: 10.3390/su15118873
|View full text |Cite
|
Sign up to set email alerts
|

Job Burnout amongst University Administrative Staff Members in China—A Perspective on Sustainable Development Goals (SDGs)

Abstract: It is widely accepted that administrative staff, as important components of a university’s workforce, play a critical role in realizing the United Nations’ Sustainable Development Goals (SDGs). The worth of administrative staff is based on their productivity, and this has a significant impact on the viability of universities. Based on the job demands–resources model, this study investigates the antecedents of job burnout among administrative staff from both emotional and interpersonal perspectives, taking into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Moreover, previous research has shown that conflicting relationships with supervisors, academic staff, and users, in addition to poor quality of communication, may contribute to WRS and impaired well-being among TAS (Biron et al, 2008;Poalses and Bezuidenhout, 2018;Foy et al, 2019). Similarly, emotional demands from work relationships (e.g., with colleagues or students) were positively associated with TAS burnout (Lei et al, 2023). With respect to the COVID-19 pandemic, PRIW has been conceptualized as an additional job demand for employees who continued working in presence or started working partly in presence and partly remotely during the pandemic (Guidetti et al, 2022).…”
Section: Risk and Protective Factors For Work-related Stress Among Ad...mentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, previous research has shown that conflicting relationships with supervisors, academic staff, and users, in addition to poor quality of communication, may contribute to WRS and impaired well-being among TAS (Biron et al, 2008;Poalses and Bezuidenhout, 2018;Foy et al, 2019). Similarly, emotional demands from work relationships (e.g., with colleagues or students) were positively associated with TAS burnout (Lei et al, 2023). With respect to the COVID-19 pandemic, PRIW has been conceptualized as an additional job demand for employees who continued working in presence or started working partly in presence and partly remotely during the pandemic (Guidetti et al, 2022).…”
Section: Risk and Protective Factors For Work-related Stress Among Ad...mentioning
confidence: 95%
“…These primarily encompass autonomy, in terms of discretion to schedule one's work (e.g., time and place) and choose the methods used to perform tasks (Jacobs et al, 2007), which is associated with reduced WRS and increased work motivation (Cropanzano et al, 2001;Jung and Shin, 2015;Kaiser et al, 2021). Moreover, organizational and social support -from supervisors and colleagues (Jolly et al, 2021) -may help prevent WRS and its negative outcomes (Cropanzano et al, 2001;Rothmann and Essenko, 2007;Foy et al, 2019;Lei et al, 2023). Other central job resources include participation in decision making, opportunities for professional and personal growth and career advancement, as well as adequate reward systems (e.g., salary, incentives, and welfare), which may positively influence TAS mental health and motivation (Biron et al, 2008;Jung and Shin, 2015;Poalses and Bezuidenhout, 2018).…”
Section: Risk and Protective Factors For Work-related Stress Among Ad...mentioning
confidence: 99%
“…Moreover, the issue of burnout is critical in today's age, where personal lives, at times, mix with work, necessitating an urgent need for reviewing workplace practices and policies [4]. In addition, employee burnout is directly related to the United Nations Sustainable Development Goals (UN-SDGs), such as ensuring healthy lives (SDG 3), promoting economic growth (SDG 8), and reducing inequalities (SDG 10) [5,6]. However, the WHO recognizing it as an occupational phenomenon within its ICD-11 manual in 2019 shifted the perception away from seeing burnout as a systemic problem, emphasizing the importance of organizational strategies in addressing this issue [7].…”
Section: Introductionmentioning
confidence: 99%
“…The high levels of working stress and multifaceted work environments they constantly confront may result in diminished well-being, either at work or outside of work. However, while prior research predominantly concentrated on the mental health of academic staff [3] and other administrative staff [4] in the university, the well-being of logistics staff was neglected.…”
Section: Introductionmentioning
confidence: 99%